Estimación de la estatura usando morfometría de los caninos, en un grupo de población colombiana - Deisi Tatiana Gómez Sepúlveda; Paula Andrea León López; Karen Yulieth Méndez Gómez; Carol Estefany Vargas Valderrama (Odontología, 2024)
Odontólogo(a)